2022
DOI: 10.1371/journal.pgen.1010245
|View full text |Cite
|
Sign up to set email alerts
|

The Caenorhabditis elegans TDRD5/7-like protein, LOTR-1, interacts with the helicase ZNFX-1 to balance epigenetic signals in the germline

Abstract: LOTUS and Tudor domain containing proteins have critical roles in the germline. Proteins that contain these domains, such as Tejas/Tapas in Drosophila, help localize the Vasa helicase to the germ granules and facilitate piRNA-mediated transposon silencing. The homologous proteins in mammals, TDRD5 and TDRD7, are required during spermiogenesis. Until now, proteins containing both LOTUS and Tudor domains in Caenorhabditis elegans have remained elusive. Here we describe LOTR-1 (D1081.7), which derives its name fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 118 publications
(151 reference statements)
1
8
0
Order By: Relevance
“…LOTR-1, another LOTUS domain-containing protein, colocalized with tagRFP::ZNFX-1 and accumulated in the Z granule, as reported previously (Fig. S2A) 44 .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…LOTR-1, another LOTUS domain-containing protein, colocalized with tagRFP::ZNFX-1 and accumulated in the Z granule, as reported previously (Fig. S2A) 44 .…”
Section: Resultssupporting
confidence: 88%
“…For instance, mutator factors, including MUT-2/RDE-3, MUT-7, MUT- 8/RDE-2, MUT-14, MUT-15/RDE-5, MUT-16/RDE-6 and RDE-8, accumulate at the Mutator foci, contributing to siRNA amplification from poly(UG)-tailed RNA templates 34,41,42 . ZNFX-1, WAGO-4, PID-2/ZSP-1 and LOTR-1 accumulate in the Z granule, promoting RNAi inheritance and piRNA-induced gene silencing 14,15,43,44 . Approximately 90 C. elegans proteins have been found to be enriched in germ granules through a variety of methods, including proteomic approaches, such as TurboID/MS and IP/MS technologies 21,27,36,45,46 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TDRD5 and TDRD7 possess LOTUS and Tudor domains and are indispensable for germ granule formation in mice 93 95 . Recent studies conducted on C. elegans established an essential role of LOTUS domain proteins in facilitating perinuclear localization of germ granules 24 , 26 , 96 . Here, using a series of microscopy and genetic experiments, we demonstrated that the LOTUS domain protein EGGD-1 is required for the proper formation of germ granule sub-compartments including P granules, Mutator foci and Z granules (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Public datasets for small RNA sequencing read for M. musculus (GSE213097 [60]), C. elegans (GSE192793 [61]), and A. thaliana (GSE152909 [62]) were used to demonstrate pipeline utility across species. We sequenced nine human cell line samples to demonstrate miRNA-loci calling.…”
Section: Pipeline Demonstration and Benchmarkingmentioning
confidence: 99%